6r-15=0+r

Simple and best practice solution for 6r-15=0+r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6r-15=0+r equation:


Simplifying
6r + -15 = 0 + r

Reorder the terms:
-15 + 6r = 0 + r
Remove the zero:
-15 + 6r = r

Solving
-15 + 6r = r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-1r' to each side of the equation.
-15 + 6r + -1r = r + -1r

Combine like terms: 6r + -1r = 5r
-15 + 5r = r + -1r

Combine like terms: r + -1r = 0
-15 + 5r = 0

Add '15' to each side of the equation.
-15 + 15 + 5r = 0 + 15

Combine like terms: -15 + 15 = 0
0 + 5r = 0 + 15
5r = 0 + 15

Combine like terms: 0 + 15 = 15
5r = 15

Divide each side by '5'.
r = 3

Simplifying
r = 3

See similar equations:

| 5x-3(x-1)=7 | | 7-3x+5when=2 | | x(x+40)=180 | | 6p+5[3(2-3p)-2(5-4p)]= | | -42=7(8-x) | | (3x-5)+(6x-40)=90 | | (3x-5)+(6x-40)= | | -7x+10=10-7x | | 4a^2-17a-15=0 | | -5y^2+8y+7=0 | | 45/6b+4111/140=4/5b-22/5+11/7 | | 8x(9x)= | | x=(x+40) | | =2+2sin(i) | | 3(2m-1)+9=6(1m+1) | | 12+9g=93 | | =2+2sinx | | -8(x+8)= | | 6(x-4)=40 | | -2a+13/5=24/5-14/5a | | 4.2p+17=3.2p+2 | | 4x^2-13x-116=0 | | -9.2=y+7.7 | | 13.75=0.25+0.50 | | 21.6+4.4t=5.32 | | 5x(-4x+4)=1 | | 18+9p12p-31= | | -13=2.7x-1.35x | | 16.331+m=38.478 | | 9g-47g-3= | | 24577=x-76x | | f(x)=8ln(x) |

Equations solver categories